UJI TERATOGENIK CAMPURAN SERBUK BIJI JINTEN HITAM (Nigella sativa L.), BIJI KELABET (Trigonella foenum-graecum L.), DAN GINSENG (Panax ginseng C. A. Mey.) PADA TIKUS PUTIH GALUR WISTAR - Christianty, Fransiska Maria; Winarti, Lina (Fakultas Kedokteran Gigi Universitas Jember, 2012)
One of the empirical effects of black cumin seed or jinten hitam (Nigella sativa L.) is the agent of abortivum. Feenugreek seeds should not be prescribed medicinally for pregnant women since they can induce uterine contraction. The objectives of this study are to know whether the flavour mixture of black cumin seed, fenugreek, and ginseng can cause abnormalities or congenital malformation to the rat foetus and also whether the congenital malformation or birth defect have relationship significantly with the dosage given. The mixing was given orally to pregnant rats on the 7th day until 15th day of pregnancy to observe the sum of foetus, living foetus, fetal death, resorption (foetus biometric) and congenital malformation (gross morphology). The results indicated that there were many effects of the mixture toward rat foetus, such as the decrease of weight and length, increase of resorption and fetal death, but statistically not significant, except weight of foetus. The dosage of 520; 1697,8; 5543,3 mg/kg of body weight didnât show abnormalities or congenital malformation.